KERAGAMAN GENETIK SUKU BANGSA JAWA DAN SUNDA BERDASARKAN PENANDA ISSR (Inter Simple Sequence Repeats) - , TENTREM LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is a country with high ethnic and cultural diversity, where the geography and culture of the tribe that different from one another. Indonesia have more 500 ethnic groups. The diversity of traits among a tribe with other tribes will allow the emergence of genetic diversity among ethnic groups in Indonesia. It is asset of knowledge which is important to study. Identification of genetic diversity can be performed using the identification of molecular markers of genetic diversity based on the characteristics of DNA (DNA fingerprinting). ISSR (Inter Simple Sequence repeats) was one of the molecular markers used for DNA analysis. This study aims to analyze the genetic diversity between Javanese and Sundanese based on molecular markers ISSR (Inter Simple Sequence Repeat), as well as analyze the genetic diversity contained in each individual in Javanese and Sundanese. There were 59 sample used in this study were genomic DNA from the blood of Javanese and Sundanese. This research by PCR methods using 3 primers of ISSR (Inter Simple Sequence Repeat) was selected. Then after having scored and analyzed PCR proceeds using the MVSP 3.1 program got polymorphism 94,47% and based on dendrogram get two main clusters with 56,3% in similarity. But clusters formed has not showed the differ markers. The research important because it can be applied to the determination of fingerprints on forensic evidence, description of the genetic map of genetic diversity, as well as the analysis of kinship among the ethnic groups in Indonesia and beyond.